![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\dfrac{2}{3}x-\dfrac{1}{2}=\dfrac{1}{10}\)
\(\dfrac{2}{3}x=\dfrac{1}{10}+\dfrac{1}{2}=\dfrac{3}{5}\)
\(x=\dfrac{3}{5}:\dfrac{2}{3}=\dfrac{9}{10}\)
b) \(\dfrac{39}{7}:x=13\)
\(x=\dfrac{\dfrac{39}{7}}{13}=\dfrac{3}{7}\)
c) \(\left(\dfrac{14}{5}x-50\right):\dfrac{2}{3}=51\)
\(\dfrac{14}{5}x-50=51\cdot\dfrac{2}{3}=34\)
\(\dfrac{14}{5}x=34+50=84\)
\(x=\dfrac{84}{\dfrac{14}{5}}=30\)
d) \(\left(x+\dfrac{1}{2}\right)\left(\dfrac{2}{3}-2x\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x+\dfrac{1}{2}=0\\\dfrac{2}{3}-2x=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-\dfrac{1}{2}\\x=\dfrac{1}{3}\end{matrix}\right.\)
e) \(\dfrac{2}{3}x-\dfrac{1}{2}x=\dfrac{5}{12}\)
\(\dfrac{1}{6}x=\dfrac{5}{12}\)
\(x=\dfrac{5}{12}:\dfrac{1}{6}=\dfrac{5}{2}\)
g) \(\left(x\cdot\dfrac{44}{7}+\dfrac{3}{7}\right)\dfrac{11}{5}-\dfrac{3}{7}=-2\)
\(\left(x\cdot\dfrac{44}{7}+\dfrac{3}{7}\right)\cdot\dfrac{11}{5}=-2+\dfrac{3}{7}=-\dfrac{11}{7}\)
\(x\cdot\dfrac{44}{7}+\dfrac{3}{7}=-\dfrac{11}{7}:\dfrac{11}{5}=-\dfrac{5}{7}\)
\(\dfrac{44}{7}x=-\dfrac{5}{7}-\dfrac{3}{7}=-\dfrac{8}{7}\)
\(x=-\dfrac{8}{7}:\dfrac{44}{7}=-\dfrac{2}{11}\)
h) \(\dfrac{13}{4}x+\left(-\dfrac{7}{6}\right)x-\dfrac{5}{3}=\dfrac{5}{12}\)
\(\dfrac{25}{12}x-\dfrac{5}{3}=\dfrac{5}{12}\)
\(\dfrac{25}{12}x=\dfrac{5}{12}+\dfrac{5}{3}=\dfrac{25}{12}\)
\(x=1\)
Mỏi tay woa bn làm nốt nha!!
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,x+\frac{3}{4}=\frac{1}{4}\)
\(\Rightarrow x=\frac{1}{4}-\frac{3}{4}=-\frac{1}{2}\)
\(b,\frac{2}{3}x-\frac{3}{7}=\frac{1}{7}\)
\(\Rightarrow\frac{2}{3}x=\frac{1}{7}+\frac{3}{7}\)
\(\Rightarrow\frac{2}{3}x=\frac{4}{7}\)
\(\Rightarrow x=\frac{4}{7}:\frac{2}{3}=\frac{4}{7}\cdot\frac{3}{2}=\frac{6}{7}\)
\(c,1\frac{2}{3}x-50\%x=-1\frac{1}{6}\)
\(\Rightarrow\frac{5}{3}x-\frac{50}{100}x=-\frac{7}{6}\)
\(\Rightarrow\left[\frac{5}{3}-\frac{50}{100}\right]x=-\frac{7}{6}\)
\(\Rightarrow\left[\frac{5}{3}-\frac{1}{2}\right]x=-\frac{7}{6}\)
\(\Rightarrow\frac{7}{6}x=-\frac{7}{6}\Leftrightarrow x=-\frac{7}{6}:\frac{7}{6}=-\frac{7}{6}\cdot\frac{6}{7}=-1\)
a,x+\(\frac{3}{4}\)=\(\frac{1}{4}\)
=>x =\(\frac{1}{4}\)-\(\frac{3}{4}\)
=> x =\(\frac{-1}{2}\)
Vậy x=\(\frac{-1}{2}\)
b,\(\frac{2}{3}\)x-\(\frac{3}{7}\)=\(\frac{1}{7}\)
=>\(\frac{2}{3}\)x =\(\frac{1}{7}\)+\(\frac{3}{7}\)
=>\(\frac{2}{3}\)x =\(\frac{4}{7}\)
=> x =\(\frac{4}{7}\) :\(\frac{2}{3}\)
=> x =\(\frac{4}{7}\).\(\frac{3}{2}\)
=> x =\(\frac{6}{7}\)
Vậy x=\(\frac{6}{7}\)
c,\(\frac{12}{3}\)x-50%x =\(\frac{-11}{6}\)
=>\(\frac{12}{3}\)x-\(\frac{1}{2}\)x=\(\frac{-11}{6}\)
=>x(\(\frac{12}{3}\)-\(\frac{1}{2}\))=\(\frac{-11}{6}\)
=>x(\(\frac{24}{6}\)-\(\frac{3}{6}\))=\(\frac{-11}{6}\)
=>x\(\frac{21}{6}\) =\(\frac{-11}{6}\)
=>x =\(\frac{-11}{6}\):\(\frac{21}{6}\)
=>x =\(\frac{-11}{6}\).\(\frac{6}{21}\)
=>x =\(\frac{-11}{21}\)
Vậy x=\(\frac{-11}{21}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1, 4[3x + 4] = 12x + 16
2, 4/3[5/3x + 6] = 20/9x + 12
3, [4/3x + 7]. 5 + 2 = 20/3x + 35 + 2 = 20/3x + 37
4, [3/7x - 6][-7] + 3x = -3x + 42 + 3x = 42
![](https://rs.olm.vn/images/avt/0.png?1311)
a; -2\(x\) - 3.(\(x-17\)) = 34 - 2.( - \(x\) + 25)
- 2\(x\) - 3\(x\) + 51 = 34 + 2\(x\) - 50
2\(x\) + 2\(x\) + 3\(x\) = - 34 + 50 + 51
7\(x\) = 67
\(x\) = 67 : 7
\(x\) = \(\dfrac{67}{7}\)
Vậy \(x\) = \(\dfrac{67}{7}\)
b; 17\(x\) + 3.(- 16\(x\) - 37) = 2\(x\) + 43 - 4\(x\)
17\(x\) - 48\(x\) - 111 = 2\(x\) - 4\(x\) + 43
- 31\(x\) - 2\(x\) + 4\(x\) = 111 + 43
- \(x\) x (31 + 2 - 4) = 154
- \(x\) x (33 - 4) = 154
- \(x\) x 29 = 154
- \(x\) = 154 : (-29)
\(x\) = - \(\dfrac{154}{29}\)
Vậy \(x=-\dfrac{154}{29}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
3x - 7 = 2x + 5
3x - 2x = 5 + 7
x = 12
|3x - 2| = 7
\(\Rightarrow\left\{\begin{matrix}3x-2=7\\-\left(3x-2\right)=7\end{matrix}\right.\Rightarrow\left\{\begin{matrix}3x=9\\-3x+2=7\end{matrix}\right.\)
\(\Rightarrow\left\{\begin{matrix}x=3\\-3x=5\end{matrix}\right.\Rightarrow\left\{\begin{matrix}x=3\\x=-\frac{5}{3}\end{matrix}\right.\)
4 - |x - 2| = -3
|x - 2| = 4 - (-3)
|x - 2| = 7
\(\Rightarrow\left\{\begin{matrix}x-2=7\\-\left(x-2\right)=7\end{matrix}\right.\Rightarrow\left\{\begin{matrix}x=9\\-x+2=7\end{matrix}\right.\)
\(\Rightarrow\left\{\begin{matrix}x=9\\-x=5\end{matrix}\right.\Rightarrow\left\{\begin{matrix}x=9\\x=-5\end{matrix}\right.\)
|2x - 3| = x - 1
\(\Rightarrow\left\{\begin{matrix}2x-3=x-1\\-\left(2x-3\right)=x-1\end{matrix}\right.\Rightarrow\left\{\begin{matrix}2x-x=-1+3\\-2x+3=x-1\end{matrix}\right.\)
\(\Rightarrow\left\{\begin{matrix}x=2\\-2x-x=-1-3\end{matrix}\right.\Rightarrow\left\{\begin{matrix}x=2\\-3x=-4\end{matrix}\right.\)
\(\Rightarrow\left\{\begin{matrix}x=2\\x=\frac{4}{3}\end{matrix}\right.\)
|3x + 1| = x + 3
\(\Rightarrow\left\{\begin{matrix}3x+1=x+3\\-\left(3x+1\right)=x+3\end{matrix}\right.\Rightarrow\left\{\begin{matrix}3x-x=3-1\\-3x-1=x+3\end{matrix}\right.\)
\(\Rightarrow\left\{\begin{matrix}2x=2\\-3x-x=3+1\end{matrix}\right.\Rightarrow\left\{\begin{matrix}x=1\\-4x=4\end{matrix}\right.\)
\(\Rightarrow\left\{\begin{matrix}x=1\\x=-1\end{matrix}\right.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1\frac{1}{2}+x=\frac{3}{2}-7\)
<=> \(\frac{3}{2}+x=\frac{-11}{2}\)
<=> \(x=-7\)
\(\frac{1}{4}+\frac{1}{3}:3x=-5\)
<=> \(\frac{1}{3}:3x=\frac{-21}{4}\)
<=> \(3x=\frac{-4}{63}\)
<=> \(x=\frac{4}{189}\)
\(\frac{4}{5}.x=\frac{8}{35}\)
<=> \(x=\frac{2}{7}\)
\(\frac{2}{3x}-\frac{1}{4}=\frac{7}{1}\)
<=> \(\frac{2}{3x}=\frac{29}{4}\)
=> \(8=87x\)
<=> \(x=\frac{8}{87}\)
\(\frac{3}{5x}+\frac{1}{2}=\frac{1}{7}\)
<=> \(\frac{3}{5x}=\frac{-5}{14}\)
<=> \(-25x=42\)
<=> \(x=\frac{-42}{25}\)
\(1-\left(5\frac{3}{8}+x-7\frac{5}{24}\right):\left(-16.\frac{2}{3}\right)=0\)
<=> \(1-\left(\frac{43}{8}+x-\frac{173}{24}\right):\frac{-32}{3}=0\)
<=> \(\frac{43}{8}+x-\frac{173}{24}=\frac{-32}{3}\)
<=> \(\frac{43}{8}+x=\frac{-83}{24}\)
<=> \(x=\frac{-53}{6}\)
học tốt
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x/7 = 6/21
x/7 = 2/7
=>x=2
b)2/3x -1/2=1/10
2/3x = 1/10+1/2
2/3x = 3/5
x=3/5:2/3
x=9/10
c)1/4+1/3 : x = -5
d)3x+17=2
đ)2/3x +1/4 =7/12
2x+3/10= 11/6 . 6/11
x : 4 1/3 = -2,5
a) Ta có:\(\left(3x-2^4\right)\cdot7^3=2\cdot7^4\)
\(\Leftrightarrow3x-16=2\cdot\dfrac{7^4}{7^3}=2\cdot7=14\)
\(\Leftrightarrow3x=30\)
hay x=10
Vậy: x=10
(3x - 24) . 73 = 2. 74
3x - 24 = 2.74 : 73
3x - 16 = 14
3x = 14 + 16
3x = 30
x = 30 : 3 = 10